Shared and distinct effects of everyday physical activity on affective well-being in schizophrenia, major depression, and healthy controls - Benedyk, Anastasia; Moldavski, Alexander; Reichert, Markus; Reinhard, Iris; Fritze, Stefan; Tost, Heike; Meyer-Lindenberg, Andreas (Journal of psychopathology and clinical science)
Novel sensor technology, such as accelerometry, enables device-based tracking of physical activity (PA) in patients’ everyday lives. In combination with intensive longitudinal self-report data, accelerometry may provide a useful tool for understanding the interactions of PA, well-being, and psychopathology. However, this interplay has not been extensively studied in severe mental illnesses (SMIs) such as schizophrenia (SZ) and major depression (major depressive disorder [MDD]). In this longitudinal prospective observational study using accelerometers, ecological momentary assessment, and clinical interviews, we applied multilevel modeling to examine the association of PA with affective well-being in patients suffering from SZ (n = 30), MDD (n = 36), and healthy controls (HCs; n = 31). We found PA to be significantly related to momentary mood in everyday life. PA was positively associated with valence (MDD, HC) and energetic arousal (SZ, MDD, HC), but negatively with calmness (SZ, MDD). Psychopathology moderated these associations across diagnoses. Patients with higher negative symptoms did not experience any valence improvement from PA, while those with higher depression scores showed no association between PA and calmness. This investigation combining accelerometry with ecological momentary assessment in SMI indicates that while PA was linked to increased energetic arousal in all participants, replicating previous results, it also showed a distinct group- and psychopathology-depended association with other mood dimensions. The observed moderation effects by negative and depressive symptoms on the association between PA, valence, and calmness, if replicated, point to a transdiagnostic phenomenon that may aid in personalizing PA interventions in SMI patients in the future. (PsycInfo Database Record (c) 2025 APA, all rights reserved)